2014
DOI: 10.1177/0049475513517117
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy with bilateral tubercular pleural effusion: challenges

Abstract: Pulmonary tuberculosis (TB) during pregnancy mimics some of the physiological changes that occur during pregnancy. Diagnosis is challenging, especially when the patient presents with acute respiratory distress. The incidence of pleural effusion in TB is 3-25% and in the majority of patients, is unilateral. We describe the intensive care management of a 27-year-old pregnant woman admitted to our hospital with life threatening respiratory distress and circulatory shock. She continued to have severe metabolic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…The search identified 4442 non-duplicate records. After title and abstract screening, as well as a full text review, 12 studies were included, as shown in Figure 1 [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], with one study included from the reference screening of a previous article [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The search identified 4442 non-duplicate records. After title and abstract screening, as well as a full text review, 12 studies were included, as shown in Figure 1 [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], with one study included from the reference screening of a previous article [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…The first concerned the diagnosis of pleural effusions, initially investigated in 1989, in 21 young subjects [ 10 ]. Effusions seemed to facilitate the determination of underlying lung lesions [ 12 ], while CUS could detect pleural effusions in early stages [ 16 ]. Secondly, CUS seemed to be accurate in detecting residual pleural thickening after evacuation [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…In general, the presence of homogeneous echogenic effusion suggests corpuscular effusion (i.e., hemorrhage or empyema), whereas an anechogenic effusion might be transudative. Since 1989, several studies demonstrated that TUS can be useful in detecting sepimentations, loculations, and thickenings of the pleura in adult patients with pulmonary TB (53)(54)(55)(56). However, these studies did not provide data on TUS sensitivity compared to radiographic "gold standard" methods.…”
Section: Pleural Effusionmentioning
confidence: 99%